Economic Development of Frontier from UE Territories of Ukraine in the Conditions of Action of Agreement About Association Ukraine-UE (Economic journal of Lesya Ukrainka Volyn National University, 2017)
Grounded, that Agreement about Association Ukraine - UE will influence in a few stages on economic development of frontier from UE territories of Ukraine. There will be an increase of volumes of trading in traditional for parties commodities on the first stage. On the second stage it costs to expect creation of far of the enterprises aimed at a duty-free export in UE of industrial products. In these regions it costs to expect to change an orientation of agriculture on the production of raw material that it will be easily directly to sell in countries UE or to sell the products of her processing there. In further it costs to expect creation of powers for redoing of this raw material in Ukraine and export of products of food industry in other countries for UE, as quotas of duty-free export in the countries of UE of this products are insignificant, and placing of enterprises from processing of the adopted types of agricultural raw material gravitates to her sources, id est to the regions of Ukraine, that abut upon the countries of UE. The real revolution will take place in development of industrial production - investors from the entire World will erect in Ukraine enterprises for the export of products in the countries of UE. It costs to expect that swingeing majority of the new enterprises oriented to the export of products in the countries of UE, it will be accommodated in the frontier regions of Ukraine, as here a  considerable role the factor of closeness will play to the market of sale on a background the factors of presence of skilled labour force with the comparatively not high remuneration of labour. Abolition of export duties on raw material will stipulate her rising in price at the Ukrainian market that will send a signal to the Ukrainian producers of raw material about expediency to the increases of her production volumes. Activity of national and local government bodies must be aimed at creation of favourable terms for investors. Except a corresponding legislation, must be paid attention on creation of corresponding technical and social infrastructure. A technical infrastructure it follows to aim at priority export industries, and social infrastructure - on preparation of workers for these industries. Further researches are perspective in direction of ground of development of infrastructure in the frontier regions of Ukraine and development of events on marketing of places.
Keywords: Agreement about Association, free trade zone, spatial organization of economy, placing of enterprises, frontier territories.